DEANOL ACEGLUMATE IN NEURASTHENIA TREATMENT IN ADOLESCENTS WITH SCHOOL DISADAPTATION - A. V. Chutko; S. Yu. Surushkina; I. S. Nikishena; E. A. Yakovenko; T. I. Anisimova (Вопросы современной педиатрии)
Aim: to study clinical manifestation of neurasthenia in adolescents with school disadaptation and to assess efficacy of deanol aceglumate in treatment of this disorder. Patients and methods: 64 adolescents aged from 14 to 17 years with neurasthenia were included into the study. Control group consisted of 64 practically healthy adolescents. Diagnostic methods: subjective scale for asthenia assessment (MFI-20), visual analogue scale for asthenia manifestations assessment (10-points scale), C. D. Spielberger’s state-trait anxiety test, vegetologic examination with A. M. Vein’s questionnaire, psychophysiological investigation with TOVA (Test of Variables of Attention), quantitative electroencephalography. Results: vegetative dysfunction, decrease of attention level and reaction speed, as well as increased level of reactive anxiety (reliably higher than in control group of healthy participants) was revealed. The results of quantitative electroencephalography demonstrated significant decrease of alpha-rhythm spectrum power in occipital leads in comparison with respective characteristic in the control group. The results of clinical and psychological studies, performed after the treatment course, showed high clinical efficacy of deanol aceglumate in this disorder in adolescents (the improvement was achieved in 44 (68,8%) of patients). Conclusions: deanol aceglumate in treatment of asthenic disorders in adolescents with school disadaptation is characterized by high efficacy. Due to absence of its influence on anxiety level, combination of this medicine with nonbenzodiazepine anxiolytics can be suggested to increase the efficacy of the treatment.